HUBUNGAN STATUS GIZI DENGAN KEBUGARAN JASMANI PADA SISWA KELAS V SD NEGERI 92 PEKANBARU - Kurniawan, Brian Dwi; ', Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Students physical fitness is important to be well-maintained. To maintain physical fitness, the students are required to work out regularly and consume healthy meal balanced in quality and quantity. As a consequence of poor nutrition or food intake, most students are less enthusiastic, often yawning, and inactive to get involved to the teacher’s lessons of physical activities in field ground. This research aims to know whether there is a correlation between nutritional status and physical fitness of grade V students of SD Negeri 92 Pekanbaru. This research implemented body weight index by height test (BB/TB) and Harvard Step Test. In collecting samples, this research implemented total sampling to the population of 62 students of grade V SD Negeri 92 Pekanbaru. This research used correlation technique. Then, the data were examined using normality test and product moment correlation test. Normality test of variable X, L0max (0.093) < Ltable (0.112), and normality test of variable Y, L0max (0.073) < Ltabel (0.112). In other words, normal data range and conclusion of this research result a relation but insignificant between nutritional status and physical fitness with correlation rxy = 0.16 that is considered as very low range based on correlation coefficient table. Therefore, Ho is accepted and Ha is rejected.Keywords: Nutritional Status, Physical Fitness